التناول السياقي العائلي لإضطراب المرور إلى الفعل لدى المراهقين - خشخوش, صالح (My University, 2023)
يتلخص مقالنا الحالي، في قراءة عيادية لإضطراب المرور إلى الفعل لدى المراهق، من منظور العلاج السياقي، حيث سيسمح لنا العلاج السياقي من خلال مجمل المصطلحات التي يقترحها فهم دور المرور إلى الفعل كعرض داخل السياق العلائقي العائلي، وسيتم لك من خلال التراث النظري للمقاربة السياقية ووضعية عيادية عايشناها خلال العلاج العائلي. Abstract : the article in hand boils down to a clinical reading of adolescent acting out disorder from the perspective of contextual therapy. Here, contextual therapy allows to understand the role of acting out as a symptom within the family relational context. This is done through the totality of terms it proposes. Also, this is done through the theoretical heritage of the contextual ans situational approach clinic witnessed during family therapy.
قراءة عيادية من منظور العلاج السياقي
مقال
Keywords: العلاج السياقي ; المراهق; adolescents, contextual therapy, acting out disorder